ANALISIS KONDISI SUHU DAN SALINITAS PERAIRAN BARAT SUMATERA MENGGUNAKAN DATA ARGO FLOAT - Juniarti, Lita; Jumarang, Muh. Ishak; Apriansyah, Apriansyah (Universitas Negeri Semarang, 2017)
A study about temperature and salinity condition in western Sumatra Sea by using Argo Float data (92o BT s.d 101 oBT dan 2o LU s.d 2o LS) has been done. This study aims to analyze the conditions of temperature and salinity, and determine the relationship of temperature and salinity in the incidence of DM (Dipole Mode). The data used is the data of temperature and salinity in the year 2004 to up 2014 the data processing Argo Float using software Ocean Data View (ODV) data in the form of Conductivity Temperature Depth (CTD), resulting in the spatial distribution of temperature and salinity, the temporal distribution of temperature and salinity, profile temperature and salinity with depth, as well as the TS diagram is then performed using the correlation equation between temperature and salinity with DMI. The results of data analysis showed that the spatial distribution of the temperature of the surface layer that is 27.5 0C to 30 0C, while the salinity is 33.5 psu to 35 psu. Spatial temperature distribution in the inner layer is 2.5 0C to 12.5 C, while the salinity is 33.5 psu to 35 psu. The temperature profile of the depth is 2.5 0C to 31 C, while the salinity is 33.25 psu to 35.5 psu. The correlation between the temperatures and the DMI shows an inverse relationship which the correlation coefecient is -0.72.